2023
DOI: 10.3389/fmolb.2023.1116868
|View full text |Cite
|
Sign up to set email alerts
|

3D interaction homology: The hydrophobic residues alanine, isoleucine, leucine, proline and valine play different structural roles in soluble and membrane proteins

Abstract: The aliphatic hydrophobic amino acid residues—alanine, isoleucine, leucine, proline and valine—are among the most common found in proteins. Their structural role in proteins is seemingly obvious: engage in hydrophobic interactions to stabilize secondary, and to a lesser extent, tertiary and quaternary structure. However, favorable hydrophobic interactions involving the sidechains of these residue types are generally less significant than the unfavorable set arising from interactions with polar atoms. Important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 80 publications
0
18
0
Order By: Relevance
“…The association of the KCNE3 TMD with lipid bilayers in the presence of mutations is also similar to that of the wild-type KCNE3. This behavior might be due to the fact that the interaction impairing mutations contain hydrophobic amino acid alanine and may favorably interact with the lipid acyl chain [38]. The interaction and dynamics properties of Nand C-termini of KCNE3 with lipid bilayers are variable with stability flexible dynamics in the presence of different interaction-impairing mutations when compared to that of the wild-type KCNE3.…”
Section: Discussionmentioning
confidence: 99%
“…The association of the KCNE3 TMD with lipid bilayers in the presence of mutations is also similar to that of the wild-type KCNE3. This behavior might be due to the fact that the interaction impairing mutations contain hydrophobic amino acid alanine and may favorably interact with the lipid acyl chain [38]. The interaction and dynamics properties of Nand C-termini of KCNE3 with lipid bilayers are variable with stability flexible dynamics in the presence of different interaction-impairing mutations when compared to that of the wild-type KCNE3.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction types are color-coded by type: green- favorable hydrophobic interactions, i.e., depicting hydrophobic interactions between the residue depicted and other atoms in its environment; purple- unfavorable hydrophobic (i.e., hydrophobic-polar) interactions; blue- favorable polar (e.g., hydrogen bonding) interactions; and red- unfavorable polar interactions. For more explanation, see the following: alanine- Ahmed et al (2019 ), isoleucine- AL Mughram et al (2023 ), serine and cysteine- Catalano et al (2021 ), phenylalanine- AL Mughram et al (2023 ), aspartic acid- Herrington and Kellogg (2021 ).…”
Section: Hint Applied To the Evaluation Of Protein–protein Interactionsmentioning
confidence: 99%
“…While our first goal was to document the interactions in which these residues engage, we were also able to develop an improved understanding of their roles in protein structure: 1) serine is considered to be somewhat more polar than cysteine but is significantly more solvent exposed; 2) while both have similarly consistent interaction roles (∼50–60% favorable polar, Figure 8 ) regardless of their accessibility, clearly very few cysteines are found on the outside of proteins; 3) it is also interesting ( Figure 8 ) that bridging (-S–S- bonded) cysteines exist in much more hydrophobic environments than their unbridged analogs, which may be mechanistically suggestive. In another more recent study, the aliphatic hydrophobic residues were examined in both soluble and membrane proteins ( AL Mughram et al, 2023 ), which surprisingly revealed somewhat modest differences in interaction profiles for these residues in soluble proteins, where they are often buried, and membrane proteins, where they are exposed to lipids. The latter is particularly important because very few X-ray crystal or even cryo-EM structures of membrane proteins retain their native lipids ( Guo, 2020 ).…”
Section: Hint Applied To the Evaluation Of Protein–protein Interactionsmentioning
confidence: 99%
“…In the case of solventexposed surface amino acids Leu or Val are represented to a lesser extent, but if present have a high probability to interact with a molecular binding partner. [37][38] Secondly, therapeutically active compounds frequently feature aromatic systems. Recent statistical analysis of physicochemical and structural properties reveal that 76 % of drugs approved within the last decade feature one or more heteroaromatic ring structures.…”
Section: Introductionmentioning
confidence: 99%